Research Cluster related to Halal Behaviour - Azzam, Hilmy Abdullah (Islamic Marketing Review, 2024)
This study aims to see the development of research on the topic of "Halal Behavior" and research plans that can be carried out based on journals published on the theme. This study uses a qualitative method with a bibliometric analysis approach. The data used are secondary data on the theme of "Halal Behavior" which comes from the Scopus database with the number of documents531journal articles. Then, the data was processed and analyzed using the VosViewer application with the aim of finding out the bibliometric map of the development of "Halal Behavior" research in the world. The results of the study found that there were 4 clusters with the most frequently used words being value, attitude, trust, consumption, satisfaction, halal cosmetic, destination, purchase intention, and industry. Then, the topics of research paths related to Halal Behavior are Consumer behavior in the halal industry, Consumers' halal product purchase intention, Muslim tourists' trust in quality, and COVID-19 and Halal food purchase behavior.